Challenges Of Implementing Occupational Safety And Health Procedures For Kayavit MSMEs Workers Upgrading To Class In Malang City, East Java, Indonesia - Elfia Nora; Sudarmiatin Sudarmiatin; Rosmiza Bidin (International Journal of Management Research and Economics, 2024)
Micro, Small and Medium Enterprises (MSMEs) need to implement occupational safety and health procedures to upgrade or go international, so that the products produced are created by workers who work below the standards of occupational safety and health that have been guaranteed by the place where they work. The purpose of this study is to find out 1) How to implement occupational safety and health procedures, especially for MSMEs workers in Kayavit Malang City, 2) Challenges faced in the implementation of occupational safety and health procedures for MSME workers in Kayavit Malang City. This type of research is a qualitative case study, with informants of MSME workers Kayavit Malang City, and business owners Data collection techniques using interviews, observation, and documentation. The results obtained from this study are, MSMEs have implemented procedures and rules for the use of work safety in the form of the use of gloves so as not to be exposed to heat production equipment and hats and workers are asked to use t-shirts when working to absorb work and be more comfortable, lighting and air circulation in the production workspace are in accordance with procedures and evaluations are carried out. The challenge faced by MSMEs in implementing occupational safety and health procedures is still the lack of workers' awareness about the importance of using personal protective equipment and implementing worker safety and health procedures to prevent accidents or risks at work.